Low‐Load Pt Nanoclusters Anchored on Graphene Hollow Spheres for Efficient Hydrogen Evolution. Issue 1 (27th September 2020) - Fan, Chuang; Jiang, Xian; Chen, Jiangyue; Wang, Xu; Qian, Shiyun; Zhao, Chenzhang; Ding, Linfei; Sun, Dongmei; Tang, Yawen
Abstract : Efficient water splitting through electrocatalysis has been studied extensively in modern energy devices, whereas the development of catalysts with high activity and stability with low‐load Pt is still a great challenge. Through the spatial confinement effect and template method, herein, hollow graphene spheres with functionalized Pt nanoclusters (Pt/GHSs) are constructed and developed as effective electrocatalysts for the hydrogen evolution reaction (HER). Electrochemical tests show that Pt/GHSs exhibit a high electrocatalytic activity and stability compared with commercial Pt/C catalysts toward HER in alkaline media. The electric double‐layer capacitance value reaches 26.0 mF cm −2, indicating that Pt/GHSs have a large electrochemically active area. Meanwhile, the load of metal Pt in the Pt/GHSs is only one‐fifth of commercial Pt/C catalysts, which significantly reduces the production cost of the catalyst. Herein a new opportunity for the low‐cost mass production of efficient and stable catalysts for practical applications is provided. Abstract : Through the spatial confinement effect and template method, hollow graphene spheres with functionalized Pt nanoclusters (Pt/GHSs) are constructed and developed as an effective electrocatalyst for hydrogen evolution reaction (HER). The outsatnding HER performance of Pt/GHSs is attributed to the synergistic effect of 3D hollow graphene archetecture and small particle size of Pt nanoclusters.